PROMOTING THE INTERNET TO STUDENTS OF SMK TRISULA DOLOK SANGGUL - Edy (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Rapidly development technology Internet Which No accompanied with education in its use causes internet addiction and tends to using the internet for useless things even negative. Because That writer do PKM with title